Efficacy of Druva Siddha Ghrita Gandusha in Management of Pittaja Mukhapaka with Special reference to Aphthous Ulcer: A Randomized Controlled Clinical Trial - Menon, Sudeep; Chakma, Haben; Patil, Dhananjay; Patil, Anuja; Chavan, Mayuri (Journal of Neonatal Surgery, 2025)
Pittaja Mukhapaka is a common condition observed among patients visiting the Ear, Nose, and Throat (ENT) outpatient department. It presents with symptoms such as oral mucosal inflammation, ulceration, and a burning sensation, often linked to Aphthous ulcers (Pittaja Mukhapaka). While modern medicine offers treatments like anti-inflammatory drugs, topical corticosteroids, and tetracyclines, these options have certain limitations. In Ayurveda, Druva Siddha Ghrita is a well-known polyherbal formulation traditionally used for oral disorders. Composed of ingredients like Jati Patra, Guduchi, Draksha, Daru Haridra, Yavasa, Haritaki, Vibhitaki, Madhu, and Amalaki, this remedy is referenced in classical texts such as Yogaratnakara and Bhaishajya Ratnavali for managing oral health issues. Materials and Methods: To assess the efficacy of Druva Siddha Ghrita in treating Mukha Rogas, a study was conducted involving 30 participants. They were randomly divided into two groups: Group A received Gandusha (oil pulling therapy) with Druva Siddha Ghrita and Madhu (honey). Group B was administered Triphala Siddha Ghrita along with Madhu. Results: Both groups showed complete relief from discomfort, burning sensations, and excessive salivation. Statistical analysis revealed a significant p-value, indicating that both treatments were equally effective. Conclusion: The study confirmed that Druva Siddha Ghrita Gandusha and Triphala Siddha Ghrita are effective in managing Pittaja Mukhapaka, providing a viable Ayurvedic alternative to conventional therapies.